Characteristics of Different Size Phytoplankton for Primary Production and Biochemical Compositions in the Western East/Japan Sea - Kang, Jae Joong; Jang, Hyo Keun; Lim, Jae-Hyun; Lee, Dabin; Lee, Jae Hyung; Bae, Hyeonji; Lee, Chang Hwa; Kang, Chang-Keun; Lee, Sang Heon (Frontiers in Microbiology, 2020)
The current phytoplankton community structure is expected to change, with small phytoplankton becoming dominant under ongoing warming conditions. To understand and evaluate the ecological roles of small phytoplankton in terms of food quantity and quality, the carbon uptake rates and intracellular biochemical compositions (i.e., carbohydrates, CHO; proteins, PRT; and lipids, LIP) of phytoplankton of different sizes were analyzed and compared in two different regions of the western East/Japan Sea (EJS): the Ulleung Basin (UB) and northwestern East/Japan Sea (NES). The average carbon uptake rate by the whole phytoplankton community in the UB (79.0 ± 12.2 mg C m–2 h–1) was approximately two times higher than that in the NES (40.7 ± 2.2 mg C m–2 h–1), although the average chlorophyll a (chl a) concentration was similar between the UB (31.0 ± 8.4 mg chl a m–2) and NES (28.4 ± 7.9 mg chl a m–2). The main reasons for the large difference in the carbon uptake rates are believed to be water temperature, which affects metabolic activity and growth rate, and the difference in euphotic depths. The contributions of small phytoplankton to the total carbon uptake rate were not significantly different between the regions studied. However, the rate of decrease in the total carbon uptake with increasing contributions from small phytoplankton was substantially higher in the UB than in the NES. This result suggests that compared to other regions in the EJS, the primary production in the UB could decrease rapidly under ongoing climate change. The calorific contents calculated based on biochemical compositions were similar between the small (1.01 ± 0.33 Kcal m–3) and large (1.14 ± 0.36 Kcal m–3) phytoplankton in the UB, whereas the biochemical contents were higher in the large phytoplankton (1.88 ± 0.54 Kcal m–3) than in the small phytoplankton (1.06 ± 0.18 Kcal m–3) in the NES. The calorific values per unit of chl a were higher for the large phytoplankton than for the small phytoplankton in both regions, which suggests that large phytoplankton could provide a more energy efficient food source to organisms in higher trophic levels in the western EJS.